User frequency and microbial contaminants of traditional oral powdered herbal formulations in Ogbomoso, Nigeria - Jennifer E. Ideh; Adepoju T.J. Ogunkunle (AOSIS, 2019)
Background: Being natural, herbal products are often perceived as safe but studies have shown that they may not be free of pathogenic microorganisms. The extent of microbial contaminants of traditional oral powdered herbal formulations (TOPHFs) in Ogbomoso, Nigeria, is not known, while the frequency of users of these drugs in the study area has not been reported. Aim: To evaluate the microbial contaminants of TOPHFs marketed in Ogbomoso Nigeria, identify the risk factors associated with their production and handling, and determine the frequency of users of the drugs. Setting: Ogbomoso, Nigeria. Methods: Fifteen manufacturers of TOPHFs listed the health conditions that are indicated for their drugs, while 125 residents provided information on their preference for those drugs. The questionnaires were analysed using descriptive statistics (frequency counts and percentages). Packaging and/or handling and level of personal and environmental hygiene of the manufacturers were examined and analysed for significance of their influence on contamination of drugs using chi-square test. Using pour plate method and following standard procedures, 12 samples of TOPHFs were analysed to quantify their bacterial and fungal contaminants. Results: The TOPHFs were indicated for 17 different types of health conditions with 60% of the sampled population being prolonged and regular users. The personal and environmental hygiene levels of the manufacturers fell short of acceptable standard. Ten out of the 12 samples analysed were heavily contaminated (i.e. above WHO limits) with yeasts/moulds and faecal coliforms such as Enterobacteria, 9 with Streptococcus and 6 with pathogenic bacterial species such as Staphylococcus and Salmonella. There was a significant association of TOPHFs contamination with manufacturers' level of formal education (p = 0.001), solid waste management (p = 0.015) and methods of updating knowledge and expertise (p = 0.004), thus making these 3 the risk factors associated with contamination of the drugs. Conclusion: Use of TOPHFs is popular among the residents of Ogbomoso, but there is a high rate of contamination of these drugs with some potentially pathogenic organisms because of insufficient quality control in their production and handling.